2015
DOI: 10.1080/03079457.2015.1058916
|View full text |Cite
|
Sign up to set email alerts
|

Increased level of protection of respiratory tract and kidney by combining different infectious bronchitis virus vaccines against challenge with nephropathogenic Brazilian genotype subcluster 4 strains

Abstract: Genotyping of seven infectious bronchitis virus (IBV) strains isolated in Brazil showed that all belonged to the common Brazilian genotype and that these strains were closest to the subcluster of strain IBV/Brazil/2007/USP-19. Pathotyping of four selected Brazilian strains showed that they all caused a considerable level of ciliostasis in the trachea but at a somewhat lower level than did M41 and Brazilian strains 50/96, 57/96, 62/96 and 64/96 representing four different serotypes that had been reported earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The GI-11 lineage has been associated with a variety of clinical conditions, ranging from respiratory disease, infertility, drop in egg production and egg quality (Chacón et al, 2011(Chacón et al, , 2008Montassier, 2010;Villarreal et al, 2007a) to enteric disorders (Villarreal et al, 2010;Villarreal et al, 2007b). It was recently demonstrated that the Brazilian variant causes predominantly respiratory and kidney diseases under experimental conditions (Chacón et al, 2014: de Wit et al, 2015. Interestingly, our phylogenetic analysis demonstrates that the indigenous GI-11 lineage has been circulating in the country since 1975, supporting the hypothesis of Montassier (2010) that this variant had already been present in the field since at least as early as 1988.…”
Section: Indigenous South American Lineagementioning
confidence: 99%
“…The GI-11 lineage has been associated with a variety of clinical conditions, ranging from respiratory disease, infertility, drop in egg production and egg quality (Chacón et al, 2011(Chacón et al, , 2008Montassier, 2010;Villarreal et al, 2007a) to enteric disorders (Villarreal et al, 2010;Villarreal et al, 2007b). It was recently demonstrated that the Brazilian variant causes predominantly respiratory and kidney diseases under experimental conditions (Chacón et al, 2014: de Wit et al, 2015. Interestingly, our phylogenetic analysis demonstrates that the indigenous GI-11 lineage has been circulating in the country since 1975, supporting the hypothesis of Montassier (2010) that this variant had already been present in the field since at least as early as 1988.…”
Section: Indigenous South American Lineagementioning
confidence: 99%
“…Since the first description of IBV in the 1930s (Schalk & Hawn, 1931), there have been a number of genotypes reported worldwide that are known to infect chicken, such as Massachusetts (Mass), Connecticut, Arkansas, 793B, It-02, QX, Q1 and Dutch strains (Jackwood, 2012). Live IBV vaccines, often two different serotypes, are co-administered to young chicks for protection against most virulent viruses (Awad et al, 2016;Chhabra et al, 2015;De Wit et al, 2015).…”
mentioning
confidence: 99%
“…This constant arising of new IB variants in different countries [8,18] is usually pointed as the main cause of vaccine failures in the field and constitutes a great challenge for the molecular direct diagnosis of IBV.Variants of IBV are mutants evolving from parental strains of this virus that differ from strains considered classic, such as those from Massachusetts group, regarding genotype, pathotype, antigenicity and/or immunogenicity. Additionally, IBV mutants are constantly subject to host immune selection and only strains with high antigenic variation are able to evade immune responses induced by vaccines and to survive in the population of hosts, leading to the development of clinical disease [25].Protection studies between commercial vaccines and IBV variants, especially those using Massachusetts (Mass) vaccines, which is the most common attenuated available vaccine, have demonstrated at least partial cross-protection by some authors [9,10,12,14,34], while another studies have not found cross-protection [7,35].Therefore, the rapid detection of IBV infection in poultry flocks and its classification between Mass and variants is considered as major challenge, which requires use of appropriate diagnostic methods. To overcome this issue, several rapid assays have been developed focusing on detection and/or characterization of S1 gene of IBV, including direct gene sequencing, RT-PCR methods with serotype-specific primers, and RT-PCR/RFLP, have become widely used, because their results correlated well with the virusserotyping [19,21,22,33].…”
mentioning
confidence: 99%
“…Protection studies between commercial vaccines and IBV variants, especially those using Massachusetts (Mass) vaccines, which is the most common attenuated available vaccine, have demonstrated at least partial cross-protection by some authors [9,10,12,14,34], while another studies have not found cross-protection [7,35].…”
mentioning
confidence: 99%